Frekwencja wyborcza w elekcjach samorządowych w Polsce - Niewiadomska-Cudak, Małgorzata (Wydział Nauk Politycznych i Dziennikarstwa UAM, 2010)
The focal point of this paper is voter turnout in the self-government elections in Poland. Particular attention is given to the turnout in the city with district rights, Łódź. This city provides an interesting place of research, both on account of its peculiar location in the center of Poland, and its recent cultural, economic and political transformation. A local referendum on the dismissal of the city mayor, held on January 10, 2010, is worth mentioning. Łódź was the first large Polish city (with a population of over 500,000) where a one-man executive organ was dismissed before the end of his term. In the paper, the results of parliamentary election turnouts are juxtaposed with self-government election turnouts. Voter turnout is analyzed for each term of the self-government in Łódź, and the types and reasons for absence are indicated. The author uses these data to emphasize that over the twenty years of self-government’s existence, voting procedures in Poland have not changed and are the most conservative in Europe.